The growing impact of niobium in organic synthesis and catalysis - Lacerda Jr., Valdemar; dos Santos, Deborah Araujo; da Silva-Filho, Luiz Carlos [UNESP]; Greco, Sandro José; dos Santos, Reginaldo Bezerra (My University, 2012)
The growing interest in, and applications of, niobium compounds in organic synthesis and catalysis are surveyed, with a focus on their efficiency and versatility in several classical and broad organic reaction types. It is our hope that this review will spur further investigations of this lesser studied, but equally important, member of group 5 transition metals. © 2012 Sigma-Aldrich Co. LLC.
Keywords: Catalysis; Efficiency; Niobium chlorides; Niobium oxides; Organic synthesis; Selectivity; Versatility